Children and Disasters: A tribute to Professor Kevin Ronan - Johnston DM; Vinnell LJ; Becker JS; Kaiser L (Massey University, 2022)
In 1997, Professor Kevin Ronan published a paper in the first ever edition of the Australasian Journal of Disaster and Trauma Studies, titled “The Effects of a “Benign” Disaster: Symptoms of Post-traumatic Stress in Children Following a Series of Volcanic Eruptions”. Over the next 23 years, Kevin and his many colleagues pursued aspects of children and disasters to both improve practice and advance scholarship in this area. In March 2020 we were saddened by the untimely passing of Kevin. As a tribute to Professor Ronan this special issue of the Australasian Journal of Disaster and Trauma Studies brings together accounts of current research and practice initiatives inspired by, building upon, and directly influenced by Professor Ronan’s work.
(c) The Author/s